Pengembangan Poster Sastra Anak Berbasis Kearifan Lokal Sumenep Untuk Siswa Kelas IV SDN Ellak Laok IV Sumenep - Yinda Shevia; Ahmad Sudi Pratikno; Umi Hanik (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Human life coexists with culture, this is because humans always try to maintain their existence in life that requires them to always be in contact with the surrounding environment. It is important for schools to reintroduce the values of local wisdom so that they can continue to strengthen local culture so that it is not lost and abandoned by the community. The purpose of this study was to produce posters of children's literature based on local wisdom sumenep for elementary school students. More specifically, the research will also explore local children's literature sources in Sumenep Regency such as legends, folklore, and fairy tales to be published in posters and then used as reading material for children's literary literacy. The method used in this study is developmental research. Development research focuses on developing systems, models, media, and products. This study used a 4-D model developed by Thiagarajan, Semmel, & Semmel (1974: 5). The development product in the form of children's literature posters based on local wisdom Sumenep aims to internalize the values of local wisdom to elementary school students through classroom learning. The test subjects in this study were grade IV students at SDN Ellak-Laok IV.